The usability of augmented reality in open and distance learning systems: A qualitative Delphi study - Altınpulluk, Hakan; Kesim, Mehmet; Kurubacak, Gulsun (Open praxis, 2020)
The main purpose of this research is to determine the usability of augmented reality in open and distance learning environments in accordance with universal design principles, and to make predictions for the future by gathering expert opinions on this subject using the Delphi technique. The Delphi technique was applied to 14 expert participants for 3 rounds as the primary data collection tool with open ended questions based on the theoretical framework. Structured interview questions were used as a secondary data collection tool and were applied during an academic exchange in China. In the Delphi technique used as the primary data collection tool, 92 themes were evaluated by experts and accepted as usability principles by end of this research. Therefore, 92 themes under 21 titles were presented for the use of augmented reality within the framework of universal design principles in open and distance learning. This research may be the first unique study on the usability of augmented reality not just as the convergence of this technology with open and distance learning environments but also incorporating the learning and communication dimensions of this convergence, thereby contributing to the literature of the field. It is imperative to determine the usability of augmented reality in open and distance learning, along with the "how" of this use in application. In this regard, the findings of this study are significant in shedding light to the enrichment, diversification and increased interaction of open and distance learning environments in accordance with universal design principles, bringing a new perspective to how a different technology convergence may be conducted, providing further accessibility.